Exploitation Againstwoman in the Novel the Woman Crying to the Black Moon By Dian Purnomo: A Study of Radical Feminism - Baiq Iling Kiranawati; Nurhadi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The theme of women is often raised in literary works. Women often experience exploitation from all sides. The research is entitled "Exploitation of Women in the Novel Women Who Cry for the Black Moon by Dian Purnomo: A Feminist Criticism Study." The problem examined in the research is the forms of exploitation of women. This research aims to describe: (1) forms of exploitation of women, (2) factors causing exploitation of women, and (3) ideas of feminism in the novel Perempuan Yang Crying to Bulan Hitam by Dian Purnomo. This research is a qualitative descriptive study. Data analysis is carried out by describing, analyzing, interpreting and concluding data. The results of this research show that: first, forms of exploitation of women, namely forced marriage, harassment and rape. Second, factors that cause exploitation of women. Namely the living environment and customs and culture. Third, feminist ideas, namely rejecting proposals, defending self-respect, and breaking off relationships.